Exploring indigenous wheat (Triticum aestivum) germplasm accessions for terminal heat tolerance - SAREEN, SINDHU; KUNDU, SUSHILA; MALIK, REKHA; DHILLON, O P; SINGH, S S (The Indian Journal of Agricultural Sciences, 2015)
Terminal heat is one of the stress factors for wheat (Triticum aestivum L.) production. Nearly 10 000 accessions of exotic and indigenous wheat germplasms are conserved in gene bank at DWR, Karnal. Four hundred and eighty-five indigenous wheat germplasm accessions were characterized as per DUS guidelines during 2007-08. Among these, 77 accessions, those bearing pale green colour, strong to medium waxiness and thousand grain weight more than 38 were preliminary evaluated for terminal heat tolerance under timely and late sown conditions during 2008-09. Genotypes with less than 20% reduction in thousand grain weight and more than 35g thousand grain weight under timely sown conditions were identified as tolerant and those with more than 40% reduction in thousand grain weight and more than 40g thousand grain weight under timely sown conditions were identified as susceptible. On this basis, 23 genotypes were identified. These along with two checks were finally evaluated under polyhouse as well as field conditions during 2009-10. Under polyhouse conditions, two sets of three replications of each genotype were sown in pots. One set was exposed to high temperature conditions in polyhouse during grain growth period. In field evaluation sowing was done under timely and late sown conditions. Data was recorded on phenological, morphological and grain traits. Data was recorded on phenological, morphological and grain traits. Five accessions namely; IC 29007B, IC 45437, IC 47993A, IC 55707B and IC 59534, had heat susceptibility index less than 1 and hence are confirmed as heat tolerant. Two of these accessions; IC 47993A, IC 55707B had high heat tolerance index. These genotypes could be used directly in breeding programme targeting for stressed environments.